Psychometric analysis of the innovative behavior scale in workers from Perú - Dominguez-Lara, Sergio (2025)
The aim of this study was to analyze the psychometric properties of the Innovative Behavior Scale (IBS) among 227 Peruvian workers (51.982% male), aged between 22 and 76 years (M = 45.009; SD = 12.046). Content validity was assessed through expert judgment regarding item clarity and relevance, while internal structure was examined using confirmatory factor analysis. Additionally, measurement invariance analysis was conducted across gender and job position, and reliability estimates were obtained for both direct scores (alpha coefficient) and the construct (omega coefficient). Results show the clarity and relevance of IBS items and a stronger empirical support for the unidimensional model, as well as acceptable levels of invariance across gender and job positions. Furthermore, reliability estimates were found to be satisfactory across all measures. In conclusion, the IBS demonstrates adequate psychometric properties.